2012
DOI: 10.5194/bg-9-1351-2012
|View full text |Cite
|
Sign up to set email alerts
|

Multifactor controls on terrestrial N<sub>2</sub>O flux over North America from 1979 through 2010

Abstract: Abstract. Nitrous oxide (N2O) is a potent greenhouse gas which also contributes to the depletion of stratospheric ozone (O3). However, the magnitude and underlying mechanisms for the spatiotemporal variations in the terrestrial sources of N2O are still far from certain. Using a process-based ecosystem model (DLEM – the Dynamic Land Ecosystem Model) driven by multiple global change factors, including climate variability, nitrogen (N) deposition, rising atmospheric carbon dioxide (CO2), tropospheric O3 p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 69 publications
2
26
0
Order By: Relevance
“…For CO 2 effect, previous studies based on model simulations (Kanter, Zhang, Mauzerall, Malyshev, & Shevliakova, ; Xu et al, ; Xu‐Ri et al, ) reported that the rising CO 2 concentration suppressed soil N 2 O emissions from land ecosystems through stimulating vegetation N uptake and possibly N use efficiency and reducing soil inorganic N concentration. However, observation‐based results diverged among ecosystem types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For CO 2 effect, previous studies based on model simulations (Kanter, Zhang, Mauzerall, Malyshev, & Shevliakova, ; Xu et al, ; Xu‐Ri et al, ) reported that the rising CO 2 concentration suppressed soil N 2 O emissions from land ecosystems through stimulating vegetation N uptake and possibly N use efficiency and reducing soil inorganic N concentration. However, observation‐based results diverged among ecosystem types.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Phillips, Whalen, and Schlesinger () reported a reduced N 2 O emissions during growing season at forest site while Moser et al () and Regan et al () suggested that atmospheric CO 2 enrichment stimulated soil N 2 O emissions in grasslands by increasing soil moisture content, and enhancing root biomass and soil biological activity. CO 2 effect on N 2 O emissions could depend on the availability of soil mineral N for plant uptake (Kanter et al, ), and then diverges among ecosystems with varied N limitation strength (Xu et al, ). However, the magnitude of CO 2 effect on N 2 O emissions is still poorly understood at the global level.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed description of these processes can be found in Tian et al (). The DLEM is capable of simulating the impacts of environmental changes (e.g., land use, climate, N deposition, atmospheric CO 2 , N fertilizer use, and manure application) on the full N cycling processes (e.g., volatilization, mineralization, immobilization, denitrification, nitrification, N leaching, and N export and uptake), and N fluxes (e.g., NH 3 , NO, N 2 O, and N 2 ) between terrestrial ecosystems and the atmosphere (Lu & Tian, ; Ren et al, , ; Tian et al, , , ; Xu et al, , ). The algorithms for NH 3 emissions in the previous version of DLEM can only simulate the unidirectional release of NH 3 from soils to the atmosphere but are unable to simulate canopy uptake and transport.…”
Section: Methodsmentioning
confidence: 99%
“…Process‐based ecosystem models applied at regional and continental scales have recently estimated that net N 2 O and CH 4 emissions increased during the past 40 years and could further increase in the future because of elevated CO 2 and temperatures (Xu et al . 2010, 2012; Tian et al . 2012).…”
mentioning
confidence: 99%